Efek Ratchet terhadap Anggaran Pemerintah Daerah: Studi pada Pemerintah Kota Se Sumatera - Vinna Novita Sari; Suhairi Suhairi; Nini Syofriyeni (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study aims to determine the Ratrchet Effect on Local Government Budgets in the City Government of Sumatra and find out which cities have the highest level of Budget Ratcheting. The research in this research is quantitative descriptive research. The data used are secondary data in the form of Regional Budget Revenue and Expenditure Reports of the City Government of Sumatra. The analysis technique in this study calculates and analyzes the Ratcheting budget with multiple linear regression analysis methods. The results of this study indicate that the Regional Original Revenue of the City Government of Sumatra Affects Regional Expenditures, Budget Ratcheting as a moderating variable strengthens the Relationship, and Palembang City is a city that has the highest Budget Ratcheting level with a percentage of 65%.